Strategi Promosi Resto “Erista Griyo Dhahar” dalam Membangun Brand Awareness - Bambang Sujarwadi; Dhety Chusumastuti; Tanaya Kanani Benedikta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The number of businesses in the culinary sector has been steadily increasing, especially after the COVID pandemic. Therefore, promotional strategies are crucial, particularly for building brand awareness in the business world.